Hexanal treatment for improving the shelf-life and quality of fruits: a review - Azhar, Aidil Hakim; Pak Dek, Mohd Sabri; Ramli, Nurul Shazini; Rukayadi, Yaya; Mediani, Ahmed; Mohd Maidin, Nurmahani (UPM Press, 2024)
Fruits are rich sources of bioactive compounds such as lycopene, tannins, β-carotene, resveratrol, and lignan. These bioactive compounds’ antioxidative, antimicrobial, and antidiabetic properties are important in the human diet. Since fruits are one of the major sources of health-promoting nutrients for human consumption, they have high economic value. Ripening is a developmental process which involves changes in the colour, texture, taste, and metabolite composition of fruits, thus affecting their quality. In the market, the good quality of fruits depends on the ripening stage. Rapid ripening could shorten the shelf-life and quality of fruits. Shortened shelf-life causes fruit spoilage during post-harvest, transport, storage, and distribution. In turn, it will cause economic losses in the fruit market. Low-temperature storage is one of the techniques to prolong the shelf-life of fruits. However, this technique requires an expensive facility to achieve and maintain the low temperature. On the other hand, it has been reported that hexanal treatment could prolong the shelf-life and quality of fruits. It is also cheaper and easier to apply. However, the ripening inhibition mechanism of hexanal is not yet fully understood. The effectiveness of hexanal treatment on different fruits is also unclear. Numerous publications on hexanal treatment reported different formulations, techniques, and effectiveness rates on different fruits. Optimised formulation and technique are important to develop an efficient hexanal treatment strategy. Therefore, the mechanism, effectiveness, formulation, technique, and development of hexanal-based products to prolong the shelf-life of fruits are discussed in this review.